Over 10% Efficient Wide Bandgap CIGSe Solar Cells on Transparent Substrate with Na Predeposition Treatment. Issue 11 (23rd September 2020) - Ould Salem, Mohamed; Fonoll, Robert; Giraldo, Sergio; Sanchez, Yudania; Placidi, Marcel; Izquierdo-Roca, Victor; Malerba, Claudia; Valentini, Matteo; Sylla, Diouldé; Thomere, Angelica; Ahmedou, Dah Ould; Saucedo, Edgardo; et al.
Abstract : With the recent rise of new photovoltaic applications, it has become necessary to develop specific optoelectronic properties for thin‐film technologies such as Cu(In, Ga)Se2 and to take advantage of their high degree of tunability. The feasibility of efficient wide bandgap absorbers on transparent conductive oxide substrates is, in that context, of critical importance. Using an original approach based on a predeposition sodium treatment, Cu(In, Ga)Se2 absorbers fabricated by sputtering and reactive annealing with a Ga to (Ga + In) content over 0.7 and an optical bandgap above 1.4 eV are deposited on transparent fluorine‐doped tin oxide films, with the insertion of an ultrathin MoSe2 layer preserving the contact's ohmicity. Different material characterizations are carried out, and a thorough Raman analysis of the absorber reveals that the sodium pretreatment significantly enhances the Ga incorporation into the chalcopyrite matrix, along with markedly improving the film's morphology and crystalline quality. This translates to a spectacular boost of the photovoltaic performance for the resulting solar cell as compared with a reference device without Na, specifically in the voltage and fill factor. Eventually, an efficiency exceeding 10% is obtained without antireflection coating, a record value bridging the gap with the state of the art on nontransparent substrates. Abstract : Using an original predeposition sodium treatment, wide bandgap Cu(In, Ga)Se2 solar cells are realized on transparent glass/fluorine‐doped tin oxide substrates with an efficiency exceeding 10%. The interplay between the alkaline element and the Ga incorporation to the CIGSe is investigated; the results open various perspectives for wide bandgap CIGSe absorbers, specifically in tandem devices and bifacial solar cells.